Enhanced larval supply and recruitment can replenish reef corals on degraded reefs. Issue 1 (December 2017) - Cruz, Dexter; Harrison, Peter
Abstract Reef-building corals have essential roles in reef ecosystems but are highly susceptible to disturbances. Increasing anthropogenic disturbances are eroding coral community resilience, leading to declining reef ecosystem function and status globally. Successful reproduction and recruitment are essential for restoring coral populations but recruitment-limitation can constrain recovery. We supplied ~400, 000Acropora tenuis larvae in fine-mesh enclosures on each of four larval-enhancement plots, comprising natural reef substrata and ten settlement tiles, on degraded reef areas in the northwestern Philippines. Initial mean total settlement on tiles in larval-enhancement plots was high (255.3 ± 68.6), whereas no larvae settled in natural control plots. Recruit survivorship began stabilising after five months, with juveniles becoming visible by eye at nine months. After three years a mean of 2.3 m−2 colonies survived within each larval-enhancement plot. Most colonies grew rapidly (16.1 ± 0.7 cm mean diameter) and spawned successfully at three years, thereby quickly re-establishing a breeding population. In contrast, natural recruitment failed to produce any new visibleA .tenuis colonies. These results demonstrate that mass larval settlement can rapidly enhance recruitment and coral recovery on degraded reef areas, and provides an important option for active reef restoration where larval supply and recruitment success are limiting.